The results influence the duration of operations in its dynamic characteristics - Петрова, Ю.В. (Proceedings of National Aviation University (archive), 2007)
Researching dynamic properties of operators by the means of the structural identification of dynamics models of human’s "visual channels” is carried out. Change of structure and parameters of dynamics models of operators’ "visual channels” during continuous action for visual perception processes from display and reproduction of visual stochastic information is considered.